The Bayeux tapestry and its contexts a reassessment - Pastan, Elizabeth Carson 1955- (Boydell studies in medieval art and architecture, 2014)
"Aspects of the Bayeux Tapestry (in fact an embroidered hanging) have always remained mysterious, despite much scholarly investigation, not least its design and patron. Here, in the first full-length interdisciplinary approach to the subject, the authors (an art historian and a historian) consider these and other issues. Rejecting the prevalent view that it was commissioned by Odo, the bishop of Bayeux and half-brother of William the Conqueror, or by some other comparable patron, they bring new evidence to bear on the question of its relationship to the abbey of St Augustine's, Canterbury. From the study of art-historical, archeological, literary, historical and documentary materials, they conclude that the monks of St Augustine's designed the hanging for display in their abbey church to tell their own story of how England was invaded and conquered in 1066"--Publisher's description